Internal Security, Cross-Border Crime, and Defense Policy in Africa: How Do Military Expenditures and Armed Forces Personnel Affect Gold-Related Customs Fraud? - Fawzi Banao (ZBW – Leibniz Information Centre for Economics, 2025)
In a context of persistent challenges surrounding border security in Africa, this study investigates the impact of defense policies on internal security by using gold-related customs fraud as a proxy for cross border crime over the period 2000–2019. Defense policy is captured through two key indicators: military expenditures and the size of armed forces personnel. The empirical strategy relies on multiple econometric techniques, including Ordinary Least Squares (OLS), Two-Stage Least Squares (2SLS), and the Generalized Method of Moments (GMM). The results reveal that both increased military spending and expansion of armed forces personnel are significantly associated with a reduction in gold-related customs fraud. Moreover, the findings indicate that expanding the size of armed forces is more effective than merely increasing defense budgets in curbing such illicit activities. The impact is particularly pronounced in the Sahel region, where intensified military mobilization leads to a more substantial decline in cross-border smuggling compared to other parts of the continent. The study concludes with a set of strategic policy recommendations, emphasizing the importance of targeted interventions in high-risk and vulnerable regions such as the Sahel.
Keywords: H56; O17; F52; 330; Gold customs fraud; Military expenditures; National armed forces personnel